NUANSA SASTRA ISLAM DALAM PENDIDIKAN ISLAM - Muhammad Abd Rahman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2021)
This study aims to find a correlation between Islamic literature and Islamic education in Indonesia in historical perception. The data are analyzed using the descrptive-analysis method by historical approach. The result showed that in Islamic literature there are values of education because of the use of literature often in the medium of the dakwah.